Accounting Practice In Hospitality Industry : A Case Study At Palace Of The Golden Horses Hotel - Mohd Amy Azhar, Hj. Mohd. Harif (1999)
Financial are the most important matters in the hospitality management. The financial and accounting matters are the core of the hotel liability that lead in planning, organizing and controlling the revenue and cost of the hotel. This research study concentrated on accounting practice in Account and Finance Department as a department that determine the hotel business as a profitable business and play a major role in strengthening the internal control relating to cost expenditure and improvement of the profit margin of the hotel. Specifically, this research study explore the accounting treatment, financial of the hotel operation that involving the internal control in the operation structure and the process of work at the Account and Finance Department, Palace Of The Golden Horses Hotel. This research study went through all the sections that under the supervision of Account and Finance Department, Palace of The Golden Horses Hotel such as Accounting Section, income Auditor Unit, Night Auditor Unit, Cashiering Unit, Credit Control Section, Account Receivable Section, Management Information System (MIS) Section, Account Payable Section, Payroll Section, Purchasing & Store (Inventory) Section and Food and Beverage Cost Control Section.